PENYADAP NIRA AREN DI KABUPATEN REJANG LEBONG - ERLIN OKTAVIANI; Erfahmi Erfahmi (Serupa The Journal of Art Education, 2020)
The purpose of making the final work is to visualize the tapping of palm sugar in Rejang Lebong district through painting work in a cubistic style while deepening the concept and improving the ability of the technique of painting. methodology used final work is the preparation step, elaboration step, synthesis step, concept realization step, and completion step. Thus manifesting ten works that visualize the difficulty and complexity in taking roomie to cook roomie into palm sugar made by palm sugar tappers with the following titles: first work “ Pedestal”. Second “ Midrib”. Third “Without Safety”. Fourth “Hit Bunches”. Fifth “Cutting Bunches”. Sixth “Cut Back”. Seventh “Bring the Bumbung”. Eighth “Put Up Bumbung”. Ninth “Towing Bumbung”. Tenth “Cooking Roomie”.Kata Kunci : Penyadap Nira Aren, Gaya Kubisme.